Distribution of type II diabetes in nuclear families. - Cook, J; Hattersley, A; Levy, J; Patel, P; Wainscoat, J; Hockaday, T; Turner, R (1993)
Type II diabetes has a substantial genetic component, but the mode of inheritance and the molecular basis of this inheritance are uncertain. This study documents the familial distribution of the disease in the parents and siblings of a consecutive series of type II diabetic subjects. We studied 66 first-degree relatives of 20 white subjects with type II diabetes and both parents alive. They were tested with a continuous infusion of glucose (5 mg.kg IBW-1.min-1) (n = 49) or FPG and hemoglobin A1c (n = 17). Seven probands had neither parent affected with diabetes or IGT, 10 had one parent affected (6 with diabetes and 4 with IGT), and 3 had both parents affected. The probands with affected and those with unaffected parents were phenotypically similar. These findings indicate that a sizable subgroup of type II diabetic subjects may have neither parent affected with a demonstrable abnormality of glucose tolerance. The assumption of autosomal dominance with complete penetrance is not supported, although it remains possible that a dominant gene of low penetrance may play a role in some pedigrees. Polygenic inheritance would appear likely, and genetic heterogeneity may occur. The inheritance of diabetic traits from phenotypically normal parents needs to be considered in the analysis of genetic linkage with type II diabetes.